Analysis of Factors that Influence Customer Loyalty in Taking People's Business Credit (KUR) at PT. Bank Sulselbar Makassar Main Branch - Zulkifli Jamid; Ria Mardiana; Sabir Sabir (Economics and Digital Business Review, 2022)
Customer loyalty is the expectation of every banking company. This study aims to analyze the effect of service, advertising, and corporate image variables on customer satisfaction. Furthermore, to analyze the effect of service variables, advertising, and company image on customer loyalty and analyze the effect of customer satisfaction variables on customer loyalty. This type of research is a quantitative research using path analysis techniques using SPSS software with path analysis techniques whose data is obtained from distributing questionnaires to 75 respondents who are people's business credit service customers. The results of the study found that service quality is always maintained, attractive advertising activities and the company's image is continuously maintained will have an impact on growing customer satisfaction so that loyalty can also be created among customers of PT. Bank Sulselbar Makassar Main Branch.